Prevalence of CTX-M Extended Spectrum B-lactamase-producing enterobacteriaceae at a private tertiary hospital in Southern Philippines. - Lucena, Mary Ann H.
The emergence of extended spectrum B-lactamase (ESBL)-producing Enterobacteriaceae is one of the growing healthcare concerns worldwide. ESBLs are plasmid encoded enzymes that confer resistance to broad-spectrum cephalosporins and monobactams. Plasmids that carry genes that code for ESBLs often carry other resistance determinants and because of these, infections caused by ESBL-producing Enterobacteriaceae are difficult to treat contributing to the problem of nosocomial infection. To evaluate the prevalence of ESBL-producing Enterobacteriaceae at Mindanao Sanitarium and Hospital in southern Philippines, Escherichia coli, Klebsiella species, and Enterobacter species isolated from clinical samples, were screened and confirmed for the presence of ESBLs. Specific primers for CTX-M, TEM and SHV ESBL enzymes were used. From a total of 583 isolates collected from September 2005 to September 2008, thirty (5.1 percent) were confirmed as ESBL-producers; the majority (60 percent) of which produce CTX-M type ESBLs. Most (89 percent) ESBL producers co-express resistance to quinolones, 61 percent are susceptible to aminoglycosides and all remained susceptible to carbapenems.
Keywords: CTX-M B-lactamases.; Enterobacteriaceae; ESBL; Prevalence; Resistance